Dampak Kecemasan Matematika (Math Anxiety) dalam Menurunnya Kinerja Belajar Siswa SD - Aisah, Siti (STKI Harapan Bima, 2025)
This study aims to analyze the role of math anxiety in the decline of elementary school students' academic performance. The study uses a quantitative method with a correlational design, involving 28 fifth-grade students from SDN Inpres Timu in Bolo District. Data were collected through a math anxiety questionnaire and students' math test scores. The results showed a significant negative relationship between math anxiety and academic performance in mathematics. Students with higher levels of math anxiety tend to achieve lower grades. This study suggests that schools and teachers should pay more attention to students' emotional aspects and implement more interactive and enjoyable teaching methods to reduce math anxiety and improve students' academic performance.